Clerical discourse: from clip to stapler (Eurasian Journal of Philology Science and Education, 2016)
This article presents traditional and modern interpretations of the discourse concept and definition of the new term clerical discourse. The brief explanation of the terms of clerical and business discourse was made in this article. The author attempts to answer the following questions about the clerical discourse forming, the importance and the level of the official language in this direction/area, clerical discourse affect on the linguistic situation and functioning of clerical discourse in general. In order to examine these questions, we used the data of documents which are formed and accompanied by clerical discourse (lexicographical sources, declarations of custom, price lists and nomenclature of office supplies, etc.). The availability of names and translations into the official language of office supplies were checked in dictionaries. We used the survey results of the three bilingual respondent groups (schoolchildren, students, respondents older than 30 years of Almaty), and sociolinguistic analyzes of results were also made.
Keywords: discourse; clerical discourse; the official language; lan¬guage planning; language policy; sociolinguistics.